Composición química y potencial biológico de una muestra de propóleos ecuatoriano. - Sánchez Elizalde, Karina Valeria (2017)
Propolis have been used since ancient times for its therapeutic benefits. Its chemical composition varies depending on geographic location, time of harvesting and producing species. The antioxidant, anti-inflammatory, antimicrobial, ant parasitic, among others have been demonstrated scientifically. However, it has also been shown that the potential of its properties, including its diverse biological activities directly dependent on its chemical composition. It is therefore essential to jointly develop chemical biological studies. Thus, this work is to evaluate the relationship between the chemical composition of a sample of propolis and its biological potential, by employing chromatographic methods, Spectroscopic and experimental biological models for the determination of possible medical uses. Chemical analyzes were performed by Thin Layer Chromatography (TLC), Gas Chromatography coupled to Mass Spectrum (GC-MS) and spectroscopy of phenolic compounds from the Folin-Ciocalteu method. The biological activities tested were: Evaluation of the antioxidant activity through radical free radical scavenger DPPH, evaluation of the antibacterial activity by diffusion method disk against Streptococcus beta-hemolytic group B, evaluation ant-parasitic activity promastigotes front Leishmania amazonensis, testing for cytotoxicity against peritoneal macrophages BALB / c mice; and determining the anti-inflammatory activity, by testing the mouse ear edema induced by 13-acetate 12-tetradecanoylphorbol. The TLC analysis revealed the presence of chromophores conjugated triterpene nature, while the development with a solution of DPPH suggested compounds with reducing ability of phenolic nature. The gas chromatographic analysis identified 47 compounds, which were analyzed by mass spectrometry testing for the presence of sugars, polyhydroxy fatty acid as general components. Fundamental analysis to identify fragments allowed eight compounds respondents structures flavones, flavanones and its variants iso, with a relative abundance of 18.47%. Being the main compounds of the sample, triterpene compounds nature ursanos, lanostanos and oleananos with 25.38% relative abundance. Other components not identified by the database of this analytical method, the analysis by more complete analytical methods for their identification being necessary. Determining phenols content by Folin-Ciocalteu proved minimal corroborating analysis by GC-MS in which I showed low relative percentage of these components. The sample showed antimicrobial activity inhibiting the growth of the strain under study beta-hemolytic Streptococcus, evaluated in conjunction with antibiotic erythromycin was used as a positive control. The anti-inflammatory activity was highly significant relative to the reference drug used in inflammatory processes which shows the potential of the sample. Assays for assessing the antiparasitic activity against Leishmania amazonensis promastigotes had low selectivity index; given the low value of the minimum inhibitory concentration which causes toxicity against mouse peritoneal macrophages. From these tests it can be suggested that the predominant nature of triterpene PE6 sample could explain the low amount of reducing substances flavonoid type and high anti-inflammatory activity obtained.